(untitled) (Research, Society and Development, 2022)
Precision agriculture is an available option for cost reduction in coffee cultivation, increasing the efficiency of fertilization, increasing profitability. In this sense, the objective of this unique work was to evaluate the distribution and chemical attributes of the soil, the production of fertilizer maps in the coffee crop, in addition to soil evaluation, the evaluation of spatial crop production and the application between fertility and the production application. The 4 years of prediction experiment at Fazenda Bela Vista, with 4 years of age experiment of Coffee Arabica 2.4, Mundo Novo 376 variety, with 3, planted in an age space of 3.5 x 1 m, totaling 2,857 plants /there is. For that, a sampling grid of 35 m x 35 m was used, totaling 24 sampling points, where 24 generated soil samples were collected, under the georeferenced canopy projection, for composite fertility analysis. The organization of the dependence of pH, M.O, Ca, Mg, V, P, K and C and, as super Simple Phosphate, Potassium Chloride, Urea and Limestone, which were presented through semivariogram. The spatial use of Kriging allowed the elaboration of maps, allowing to observe the variability and carry out the management in a localized and precise way. It could be seen that the difference in chemical attributes in the common and conventional techniques of precision agriculture, in the same way is each of the differences to be applied.